MENINGKATKAN KEEFEKTIFAN PEMIMPIN GUNA MENINGKATKAN KEPUASAN KERJA KARYAWAN DI DINAS PENDIDIKAN PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Astuti, Hesti Widi (Jurnal Manajemen dan Keuangan, 2009)
This is watchfulness done at province education official, where does population administration, program build area, educational incredible and junior school , intermediate educational, high school, educational informal school, functional group. data collecting technique is done with interview and distribution quesioner.Variable used in watchfulness that is leader effectiveness variable (connection leaderhsip-anggota, position power, task structure) and employee work satisfaction variable.Conclusion in this watchfulness, follow leadership: leader effectiveness at province education official mey good; while follow employee: based on watchfulness result shows that at province education official mey has leader less effective. watchfulness result shows that value mean work satisfaction variable ranges from 2,9655 until 3,8793. value show that in general respondent feels work satisfaction enough, but not yet optimal. score lpc follow employee enough, with value mean 3,1724 until 3,5862.Keyword : leader effectiveness, work satisfaction.